Surat Al-Baqarah Definition and Clarification of its Issues (Islamic Sciences Journal, 2023)
ABSTRACT               Praise be to Allah, Lord of the worlds, and blessings and peace be upon our master Muhammad, his family and all his companions. As for after. the Holy Qur’an is a heavenly message, the most prestigious, and the greatest miracle, and it was completed by a system and method, It is a book of guidance and the constitution of a nation (it is the best of a nation that brought people out) and it is the source of all wisdom. and the metal of every virtue, In it is the news of what came before us, the news of what comes after us, and the judgment of what is between us, and it is the separation and not the joking. Allah fragments any giant who leaves it. Any person who wishes guidance other than the Holy Quran will be misleaded. The Holy Quran is the straight and right way which no one suspects it or be confused within it.Scientists still in need of it and its miracles do not end . The Holly Quran represents the best time and effort exerted by scientists as well as scholars .Taking care of the Holly Quran is a recitation ,study, teaching, exegesis, and deduction from the impositions of adequacies.
Keywords: The cow, the number of its verses, its virtues, its importance, aspects of knowledge